2020
DOI: 10.3390/ijerph17196987
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Job Demands and Resources Associated with Compassion Fatigue in Mental Health Professionals

Abstract: Psychosocial hazards in mental healthcare contribute to the development of compassion fatigue in mental health professionals. Compassion fatigue has a negative impact on the mental health and wellbeing of professionals that can impair the quality of services provided to clients. The majority of research on compassion fatigue has focused on individual-level variables such as gender, history of trauma and age, among others. It is also imperative to understand the role played by alterable work-related characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 125 publications
(372 reference statements)
3
50
1
2
Order By: Relevance
“…In our results, dependence relations emerged concerning compassion satisfaction and all suppression factors. Even in this case, the significant dependences highlighted the role of suppression with reference to the opportunity to experience compassionate clinical circumstances (Zeidner et al, 2013;Ivicic and Motta, 2017;Singh et al, 2020). The role of compassion is currently emerging as a high influencing factor, both related to clinicians and patients and extended to several conditions such as psychopathology, therapy, mental health, image concerns, neurovegetative phenomena, and general health outcomes (Mincȃ et al, 2013;Rosa et al, 2019;Carter et al, 2021;Kim et al, 2021;McKay and Walker, 2021;Turk et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…In our results, dependence relations emerged concerning compassion satisfaction and all suppression factors. Even in this case, the significant dependences highlighted the role of suppression with reference to the opportunity to experience compassionate clinical circumstances (Zeidner et al, 2013;Ivicic and Motta, 2017;Singh et al, 2020). The role of compassion is currently emerging as a high influencing factor, both related to clinicians and patients and extended to several conditions such as psychopathology, therapy, mental health, image concerns, neurovegetative phenomena, and general health outcomes (Mincȃ et al, 2013;Rosa et al, 2019;Carter et al, 2021;Kim et al, 2021;McKay and Walker, 2021;Turk et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…Prior to COVID-19, these professionals already experienced high levels of institutional stress with large caseloads, chronic understaffing and turnover as the norm ( Paris & Hoge, 2010 ; Rupert & Morgan, 2005 ). High doses of indirect trauma exposure for these professionals including foster parents were common as was the risk for developing symptoms of secondary traumatic stress (STS) and related conditions such as burnout ( Bridger et al, 2020 ; Cieslak et al, 2014 ; Hannah & Woolgar, 2018 ; Singh et al, 2020 ; Whitt-Woosley et al, 2020 ). Emerging research on the effects of COVID-19 related stressors and experiences of STS and burnout in professionals and caregivers in foster care found statistically significant increases in STS related symptoms from pre-pandemic baseline to summer 2020 in addition to frequent experiencing of numerous COVID-19 related stressors (blinded for review).…”
Section: Pandemic-related Impacts On Professionalsmentioning
confidence: 99%
“…Taken together, previous research has demonstrated that it is possible to predict CF (Singh et al, 2020;Turgoose & Maddox, 2017), but it is unclear how important these predictors are and how well the non-linear predictive models perform. Moreover, due to the limitation of conventional statistical methods, most studies investigated only one or several predictors of CF and have not obtained the patterns of CF.…”
Section: Introductionmentioning
confidence: 97%